The costs comparison of producing, exploitation and utilization of renewable, nuclear and non-renewable energy - Krychkovskyi, Taras (Technology audit and production reserves, 2018)
The object of research is the methods for comparing the cost of production, operation and utilization of renewable, nuclear and non-renewable energy. One of the most problematic places in determining which energy is the cheapest is that different authors focus on various aspects of the assessment of energy sources. Some scientists focus solely on the cost of building a certain type of power plant, others on the cost of utilization or the cost of operation. However, there is no single approach that would eliminate the shortcomings of previous studies and estimate the cost of various energy resources in a comprehensive manner. The approach to the study will be based on the methods of analysis, comparison, observation and synthesis, will eliminate some of the shortcomings that were inherent in the previous study, and consider the issue of the cost of energy resources more comprehensively. The result obtained in this work allows to look at the problem of estimating the cost of energy resources more widely and better understand which energy technology is the cheapest, in terms of price, not only during creation, use and disposal, but in general. This is due to the fact that the proposed method of estimating the cost has a number of features, including the cost of nuclear, renewable and non-renewable energy from three points of view: the cost of creating technology, use and disposal. This ensures the possibility of obtaining a much broader view of this issue and a deep understanding of the advantages and disadvantages of each type of energy technology at each stage of use. With the help of identifying weaknesses and strengths, as well as opportunities and threats, the results of the study and generalization obtained using the SWOT analysis in tables are analyzed. Compared with similar well-known studies, this provides a deeper understanding of which energy technology is truly the best.